Cauchy problem for an essentially infinite-dimensional parabolic equation with variable coefficients - Bogdanskii, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
The Cauchy problem for the equation ut = L_x u = j(x) (u_x’’) with positive essentially infinite-dimensional functionals j(x) is studied in a certain Banach space of functions on an infinite-dimensional separable real Hilbert space.